Decolonizing linguistics - Charity Hudley, Anne H.; Mallinson, Christine; Bucholtz, Mary 1966- (Oxford University Press, 2024)
Decolonizing Linguistics, the companion volume to Inclusion in Linguistics, is designed to uncover and intervene in the history and ongoing legacy of colonization and colonial thinking in linguistics and related fields. Taken together, the two volumes are the first comprehensive, action-oriented, book-length discussions of how to advance social justice in all aspects of the discipline.